As Múltiplas territorialidades do Festival de Música de Ourinhos - Santos, Gabriela Cabral [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This course conclusion work aims to develop and analyze various territorialities (Haesbaert, 2006) Music Festival Ourinhos identifying key historical and geographic influences and impacts that this event produces within the municipality. Therefore, at the methodological level, through interviews, questionnaires and photographs, we will seek to understand the social, economic and cultural expression of the Festival through their main actors and social groups that define their territoriality. The main issue is to be placed as an inclusive or segregated nature of this event in the context of local society. The Ourinhos Music Festival is held by the municipal Department of Culture and is now in its fourteenth edition in 2014. Its general structure is based on designs created by municipal agency seeking the preservation of cultural and musical memory, involving bands, radio shows, schools and musical groups who are dedicated to music, besides being physically installed in libraries and public parks, cultural centers, municipal theater, municipal schools, bars and business houses of the city

O presente trabalho de conclusão de curso pretende desenvolver e analisar as diversas territorialidades (HAESBAERT, 2006) do Festival de Música de Ourinhos, identificando as principais influências e impactos históricos e geográficos que esse evento produz no espaço do município. Portanto, no plano metodológico, através de entrevistas, questionários e fotografias, buscaremos compreender a expressão social, econômica e cultural do Festival através de seus principais atores e grupos sociais que definem suas territorialidades. A problemática principal a ser colocada é quanto ao caráter inclusivo ou segregador desse evento no contexto da sociedade local. O Festival de Música de Ourinhos é realizado pela Secretaria municipal de Cultural e se encontra em sua décima quarta edição em 2014. Sua estrutura geral se baseia em projetos criados pelo órgão municipal buscando a preservação da memória cultural e musical, envolvendo bandas, programas de rádio, escolas e grupos musicais que se dedicam à música, além de fisicamente estar instalado em bibliotecas e praças públicas, centros culturais, teatro municipal, escolas da rede municipal, bares e casas comerciais da cidade
Keywords: Territorialidade humana; Festivais de música; Ourinhos (SP)